2017
DOI: 10.1093/mnras/stx1077
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity calibrations for dwarf stars and giants in the Geneva photometric system

Abstract: We use the most homogeneous Geneva seven-colour photometric system to derive new metallicity calibrations for early A-to K-type stars that cover both, dwarf stars and giants. The calibrations are based on several spectroscopic data sets that were merged to a common scale, and we applied them to open cluster data to obtain an additional proof of the metallicity scale and accuracy. In total, metallicities of 54 open clusters are presented. The accuracy of the calibrations for single stars is in general below 0.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…On the basis of 12 main-sequence stars, we find the metallicity [Fe/H] NLTE = −0.10 ± 0.02 dex and [Fe/H] LTE = −0.09 ± 0.03 dex. This estimate is consistent, within the uncertainties, with estimates based on the analysis of high-resolution spectra by Santos et al (2012), Conrad et al (2014), andNetopil (2017). Fritzewski et al (2019) reported the metallicity of [Fe/H] of −0.07 ± 0.10 dex using lower-resolution near-IR spectra.…”
Section: Ngc 3532supporting
confidence: 89%
“…On the basis of 12 main-sequence stars, we find the metallicity [Fe/H] NLTE = −0.10 ± 0.02 dex and [Fe/H] LTE = −0.09 ± 0.03 dex. This estimate is consistent, within the uncertainties, with estimates based on the analysis of high-resolution spectra by Santos et al (2012), Conrad et al (2014), andNetopil (2017). Fritzewski et al (2019) reported the metallicity of [Fe/H] of −0.07 ± 0.10 dex using lower-resolution near-IR spectra.…”
Section: Ngc 3532supporting
confidence: 89%
“…The estimated equatorial velocity and rotation period are also close to the solar values (e.g., v sin i = 2.4 km s −1 , P rot = 21.4 d, Hojjatpanah et al 2020). The metal content is slightly higher than the solar value with different estimates ranging from [Fe/H]=0.31 to 0.37 (Netopil 2017;C ¸elebi et al 2019). The star does not have companions of stellar mass, with observational limits in separation and magnitude difference ranging from ρ = 0.03 ′′ at ∆mag = 0 to ρ = 1.5 ′′ at ∆mag = 3.0 (Tokovinin 2014).…”
Section: δ Pav a Nearby Solar Twinsupporting
confidence: 72%
“…Basic physical parameters of the primary G0V star have been determined by Netopil (2017) and by Luck (2017). The two studies give similar values for T eff and log g. We tabulate Luck's values, and use the differences between the two studies to estimate uncertainties.…”
Section: Physical Parameters Of the Starsmentioning
confidence: 99%